Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae) - Zhao, Shuai; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2020)
Two new species from China are described and illustrated, Sinodorcadion chinense Xie & Wang sp. nov. from Hubei and Sinodorcadion zenghuaae Xie & Wang sp. nov. from Guangxi. A key to species of the genus is presented.